2017
DOI: 10.1097/mco.0000000000000399
|View full text |Cite
|
Sign up to set email alerts
|

Whats ‘App-ening’

Abstract: eHealth solutions for digestive diseases have a supportive function and a positive impact on patients. However, there is a need to increase patient education and further develop the possibility for care team-patient communication within eHealth solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…eHealth offers patients a quick and easily understandable tool for disease monitoring, with faster recognition of disease relapse, greater engagement with their treatment and easier access to health care. All of these benefits support patients in optimizing their individualized treatment[10,11]. Close monitoring of disease activity is vital for optimizing individualized treatments and to improve potentially the long-term disease course.…”
Section: Introductionmentioning
confidence: 99%
“…eHealth offers patients a quick and easily understandable tool for disease monitoring, with faster recognition of disease relapse, greater engagement with their treatment and easier access to health care. All of these benefits support patients in optimizing their individualized treatment[10,11]. Close monitoring of disease activity is vital for optimizing individualized treatments and to improve potentially the long-term disease course.…”
Section: Introductionmentioning
confidence: 99%
“…However, symptoms vary widely, with diarrhoea and/or constipation being present or absent in the different subtypes, and symptoms of bloating and flatulence are often present [ 1 ]. Symptom tracking is often lacking in apps for gut disease [ 27 ]; however, this function provided an opportunity for participants to monitor their progress during the different stages of the low FODMAP diet.…”
Section: Discussionmentioning
confidence: 99%
“…Although data on the use of barcode scanning was not available, this app demonstrated that at least 85% of participants utilised the free text and food category functions. Thus, apps that incorporate a vast branded product database have the potential to increase knowledge and potentially confidence regarding which foods can be consumed during the low FODMAP diet [ 27 , 42 ], which is often of great concern to patients who do not have access to a dietitian [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations